"Beyond the Four Walls of My Building": A Case Study of #Edchat as a Community of Practice. Issue 1 (2nd January 2016) - Britt, Virginia G.; Paulus, Trena
ABSTRACT: Although Twitter and other social media sites have grown in popularity with educators, we still do not know what is happening within this online space or how it supports teachers. The purpose of this case study of #Edchat, a group of educators who meet weekly on Twitter, was to investigate informal professional development through the lens of communities of practice theory. Chat observations, participant interviews, and archival documents were analyzed. #Edchat reflected some aspects of a community of practice, including overlap in the description of who belongs, sustained mutual relationships, absences of introductory preamble in the conversations, quick setup of a problem to be discussed, and a rapid flow of information. The authors explore how these indicators overlap with best practices in professional development and recommend that administrators learn from what is happening in social media spaces as they work toward supporting teacher learning.